Endoscopic Transverse Gastrocsoleus Recession in Children With Cerebral Palsy - Kim, Dae-Wook; Kim, Hyun Woo; Yoon, Ji-Yeon; Rhee, Isaac; Oh, Min-Kyung; Park, Kun-Bo (Frontiers in Pediatrics, 2020)
Aim: The aim of this study was to evaluate the surgical outcome, in terms of gait improvement, of endoscopic transverse Vulpius gastrocsoleus recession in children with cerebral palsy compared to the traditional open surgery. Methods: Twenty-seven children with cerebral palsy who had undergone endoscopic transverse Vulpius gastrocsoleus recession were reviewed. For the comparison of gait improvement, independent ambulatory spastic diplegic patients who had undergone only endoscopic transverse Vulpius gastrocsoleus recession on both legs were selected. Seven (14 legs) children were included and the median age was 7 years (6–9 years). Seven age-matched patients with the same inclusion/exclusion criteria who underwent open surgery were selected as the control group. Physical examination and gait parameters were evaluated and compared between groups, including the gait deviation index (GDI), and gait profile score (GPS). Results: There was no significant complication in twenty-seven children after endoscopic transverse Vulpius gastrocsoleus recession. However, one patient required a revision open surgery at postoperative 1 year 9 months due to the recurrence of equinus and the incomplete division of the midline raphe which was noted during surgery. When comparing gait improvements, there were no differences between the endoscopic and open surgery groups in ankle dorsiflexion angle, ankle kinetics, GDI, and GPS. The postoperative peak ankle dorsiflexion during stance phase was slightly higher in the open group. Conclusion: This is the first study that evaluates gait improvement exclusively for children with spastic diplegia after endoscopic transverse Vulpius gastrocsoleus recession. The gait improvements after endoscopic surgery were comparable to the open surgery, however, the possibility of reduced improvement in ankle kinematics should be considered.